Efficacy of the Gulu University Reproductive Health Simulation Training for final year medical students and interns: a before-and-after study - Pebalo Francis Pebolo; Jerom Okot; Felix Bongomin; Silvia Awor; Baifa Arwinyo; Sande Ojara; Jimmyy Opee; Ayikoru Jackline; Eric Ssennuni; Simple Ouma (SAGE Publishing, 2024)
Background: Reproductive health emergencies, such as postpartum hemorrhage, contribute significantly to maternal and neonatal morbidity and mortality in Uganda due to knowledge and skills gaps. Medical interns, intern midwives, and nurses are crucial as frontline healthcare workers in responding to these emergencies. Our proposed hands-on strategy involves comprehensive simulation-based training (SBT) to equip these healthcare workers with the essential knowledge to manage common reproductive health emergencies and procedures in the country. Objectives: The study aimed to assess the effectiveness of comprehensive SBT in improving the knowledge of interns and fifth-year medical students on reproductive health emergencies and procedures at Gulu University and its Teaching Hospitals in Uganda. Design: A before-and-after study. Methods: A 4-day SBT was conducted for fifth-year medical students and interns (nurses, midwives, and doctors) at Gulu University Teaching Hospitals, focusing on reproductive health emergencies. Pre- and post-tests with 40 multiple-choice questions were used to evaluate knowledge enhancement, the scores were summarized as medians and interquartile ranges. Paired sample t -tests was used to test the difference in pre- and post-test scores. Independent sample t -tests compared median post-test results between interns and students, with a p -value <0.05 considered significant. Results: A total of 153 participants were enrolled, the majority being males (78.4%, n  = 120) and medical students (73.9%, n  = 113). Among the 40 interns, 55% ( n  = 22) were doctors, 30% ( n  = 12) were midwives, and 15% ( n  = 6) were nurses. The study participants showed an increase in knowledge, with median post-test scores higher than pre-test scores for all participants [63% (interquartile ranges, IQR: 57-71%) versus 49% (42-54%), with a median difference of 14% (8-23%), p  < 0.001]. Conclusion: The SBT effectively imparts key knowledge competencies to the interns and fifth-year medical students. We recommend that SBT be included as part of the course units that students should take and for continuous medical education for qualified healthcare workers in resource-limited settings.